2021
DOI: 10.3389/fcvm.2021.720581
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Protects Against Atrial Remodeling via Reducing Oxidative Stress

Abstract: Aim: The structural and electrical changes in the atrium, also known as atrial remodeling, are the main characteristics of atrial fibrillation (AF). Fibroblast growth factor 21 (Fgf21) is an important endocrine factor, which has been shown to play an important role in cardiovascular diseases. However, the effects of Fgf21 on atrial remodeling have not been addressed yet. The purpose of the present study is to evaluate the effects of Fgf21 on atrial remodeling.Methods and Results: Adult mice were treated with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Then, we used rmFGF21 to signi cantly improve cardiac echocardiography and serological indexes after overexpression of FGF21 in HF models, suggesting a signi cant improvement in cardiac function, and further veri ed the cardiac protective effect of FGF21 in HF. This is consistent with the conclusions reported in the literature, which found that FGF21 can improve the function of failing heart by increasing LVEF and LVFS and decreasing serum BNP levels [19,20] .…”
Section: Discussionsupporting
confidence: 93%
“…Then, we used rmFGF21 to signi cantly improve cardiac echocardiography and serological indexes after overexpression of FGF21 in HF models, suggesting a signi cant improvement in cardiac function, and further veri ed the cardiac protective effect of FGF21 in HF. This is consistent with the conclusions reported in the literature, which found that FGF21 can improve the function of failing heart by increasing LVEF and LVFS and decreasing serum BNP levels [19,20] .…”
Section: Discussionsupporting
confidence: 93%
“…It was found that the cardioprotective effect of FGF21 was limited due to its low expression in the normal heart ( Chen et al, 2021 ). Once the heart is exposed to multiple stimuli such as ischemia and hypoxia, inflammation, oxidative stress, lipotoxicity and endoplasmic reticulum stress, the secretion of FGF21 is significantly increased to fully play a cardioprotective role ( Planavila et al, 2013a ; Planavila, Redondo-Angulo & Villarroya, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen M found that by increasing antioxidant genes such as SOD2 and UCP3, fibroblast growth factor 21 successfully reduced atrial remodeling by lowering oxidative stress. 46 In addition, Wang et al revealed that CXCR4 expression is increased in chronic AF patients with mitral valve dysfunction, that it is related with atrial remodeling. 47 However, no difference in the expression of PDK4, S100A12, RASD1, or DDIT4 was seen between AF patients and HCs.…”
Section: Discussionmentioning
confidence: 99%